Endoscopic Multipoint Laser System for Objective Pediatric Airway Assessment. (June 2021) - Hall, Andrew Christopher; Navaratnam, Annakan Victor; Maughan, Elizabeth; Hartley, Benjamin; Hewitt, Richard J.; Butler, Colin
Recent technological advances within aeronautical engineering have demonstrated the delivery of objective quantitative endoscopic measurements to within one-hundredth of a millimeter. We sought to validate this emerging laser technology in a simulation-based assessment of pediatric airway stenosis. A 4.4-mm flexible endoscope, incorporating a laser measurement system projecting 49 laser points into the endoscopic view, was used to assess a simulated model of subglottic stenosis. Multiple anteroposterior and lateral measurements were obtained for each stenosis and compared with standard airway assessment techniques. Intra- and interobserver reliability was assessed. A total of 240 multipoint laser measurements were obtained of simulated airway stenosis. The mean difference from manual measurement was 0.1886 mm. The Bland-Altman plot showed low bias (0.011) and narrow 95% limits of agreement (−0.46 to 0.48). This advanced endoscopic measurement technique shows great promise for clinical development to benefit ongoing assessment and treatment of evolving pediatric airway stenosis.